Open Government data use by Malaysian researchers: some empirical evidence - Zainal, Noor Zalina; Hussin, Husnayati; Abd Rahim, Noor Hayani; Mior Nazri, Mior Nasir; Suhaimi, Mohd Adam (IEEE Computer Society, 2019)
Sharing data by the government with citizens will lead to a more transparent and trustworthy government. Open Government Data (OGD) has been initiated by many governments worldwide aiming to publicly and freely share government data via online. In a similar effort, the government of Malaysia has launched an OGD portal in 2014 and currently more than 12,000 data sets are available for citizens and businesses to access. However, there is a concern on the level of usage of these datasets. Additionally, there is lack of empirical studies done to understand this issue. The purpose of this study is to fill this gap. Based on a questionnaire survey method, data was collected from Malaysian researchers and academicians to understand their use of OGD. Despite a rather small sample of 62 responses, the findings shed light on the access and purposes of using OGD in the Malaysia context.